The challenges in classifying the vulnerabilities of the Yanomami territory: A stage in the workforce sizing methodology (Research, Society and Development, 2025)
This study aims to present the challenges experienced in the selection of epidemiological indicators to classify vulnerabilities in the health territories of the Yanomami people. This is a descriptive study, an experience report, focusing on the analysis and selection of specific indicators that made it possible to diagnose the health conditions of these population groups and local health needs. It represents one of the stages in the development of the proposed methodology for planning and sizing the multidisciplinary workforce for indigenous health, with the participation of workers and managers from the Yanomami Special Indigenous Health District, the Secretariat of Indigenous Health and the Secretariat of Labor and Health Education Management. Six epidemiological indicators were identified and selected: infant mortality in children under one year of age and nutritional deficit in children under five years of age, taking into account the reliability, potential and availability of information from official sources. Vulnerabilities were classified based on the simple arithmetic average between each indicator, with scores ranging from one to three being assigned among the 67 health establishments in the territory, resulting in three levels of vulnerability classification: high, very high, very high.